IMPLEMENTASI PEMBELAJARAN PAK BERBASIS MULTIKULTURAL DALAM MEMBINA SIKAP TOLERANSI SISWA DI SEKOLAH - Ondja, Helbert Igilemba; Kuanine, Melyarmes Hodner; Harefa, Samadaya; Metboki, Rianto Junedi Agustan (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2023)
This article discusses the implementation of multicultural-based PAK learning in fostering students at school. The author uses literature study to discuss the topic. From the results of the analysis of several sources of literature, a specific description of the realization of student tolerance is inseparable from the role and position of the teacher in the school. The teaching of the Lord Jesus related to tolerance is to love your fellow human beings as yourself. Humans as neighbors must be seen and treated as objects of love where the measure of treatment for others knows no boundaries of religion, ethnicity and race but must be based on love. PAK teaches the fear of God and respect for others and helps each other sincerely regardless of class and background. For this reason, the role of PAK needs to be emphasized in the form of presenting learning materials that are in accordance with the needs of the diversity of students in schools. So that students, teachers and everyone involved in PAK can realize the teachings of Jesus in an attitude of helping fellow human beings.